INCREASING WELL PERFORMANCE EFFICIENCY USING INTEGRATED SIMULATION TOOLS - Denis N. Zhigalov; Vladimir V. Poplygin (Известия Томского политехнического университета: Инжиниринг георесурсов, 2022)
The relevance of the work is in the need for a comprehensive analysis of the oil asset, both of its current and the long run status. This will allow more efficient well stock operation with consideration for the changes of the formation performance indicators. Objective: determining the date of wells’ natural flowing completion, and where possible, proposing measures to extend their work at the depletion drive; select the necessary downhole pumping equipment for further artificial lifting; perform sensitivity analysis of the selected equipment. Objects: oil field at the first development phase; digital models of the gathering system, reservoir pressure support system, production and injection wells, reservoir developed using the material balance method. Through combination of these models, an integrated field model used for operational calculations was obtained. Methods. Integrated modeling tools have been used for comprehensive assessment of calculations. This technique makes it possible to consider the constraints imposed by both surface infrastructure and reservoir. Optimization calculations was also made to extend the life of wells at the depletion drive. An approach was developed for selection of downhole pumping equipment, taking into account the performance indicators. The sensitivity analysis technique for the selected downhole pumping equipment was described. Results. The authors carried out the forecast calculation, identified wells, which will stop naturally flowing in the near future. With the help of multivariant optimization calculations, the measures to extend the well flowing period were proposed. Downhole pumping equipment was also selected for such wells. A feasibility study of the proposed activities was performed.